2008
DOI: 10.21273/jashs.133.2.188
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Physiological Responses to Drought Stress in Four Oleander Clones

Abstract: Oleander (Nerium oleander L.), native to southern Asia and the Mediterranean region, is a fast-growing evergreen shrub planted widely in the southern United States. A greenhouse study was conducted to quantify the growth and physiological responses of two cultivars, Hardy Pink and Hardy Red, and two breeding lines, EP1 and EP2, of oleander to a 12-week cyclic drought stress. Drought stress was imposed by irrigating the plants to near container capacity and then withholding ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 31 publications
5
25
0
Order By: Relevance
“…For example, RSR was higher in drought-stressed rice (Oryza sativa) compared with the well-watered plants (Xu et al, 2015). Similar results were reported in other crops, including oleander [Nerium oleander (Niu and Rodriguez, 2008)], cotton [Gossypium hirsutum (Pace et al, 1999)], and arabidopsis [Arabidopsis thaliana (Durand et al, 2016)]. Huang and Gao (2000) reported an increased proportion of 14 C allocated to the root than shoot in tall fescue cultivars under the soil drying condition, with a greater increase in tolerant cultivars, and a higher proportion in the deeper root.…”
Section: Discussionsupporting
confidence: 70%
“…For example, RSR was higher in drought-stressed rice (Oryza sativa) compared with the well-watered plants (Xu et al, 2015). Similar results were reported in other crops, including oleander [Nerium oleander (Niu and Rodriguez, 2008)], cotton [Gossypium hirsutum (Pace et al, 1999)], and arabidopsis [Arabidopsis thaliana (Durand et al, 2016)]. Huang and Gao (2000) reported an increased proportion of 14 C allocated to the root than shoot in tall fescue cultivars under the soil drying condition, with a greater increase in tolerant cultivars, and a higher proportion in the deeper root.…”
Section: Discussionsupporting
confidence: 70%
“…This was considered beneficial for adaptation and surviving a water stress situation (Blum, 1996). Angelonia, heliotrope, carnation, crimson bottlebrush (Callistemon citrinus), geranium (Pelargonium ·hortorum), impatiens, and oleander (Nerium oleander) were reported to have a higher root density or root-to-shoot ratio with lower SMC ( Alvarez et al, , 2011Chyli nski et al, 2007;Guo et al, 2018;Niu et al, 2008;S anchez-Blanco et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Chl fluorescence parameters are often used to indicate the extent of damage to the photosynthetic apparatus (Niu et al 2008). In the present study, CaCl2-treated P. ostii F0 was significantly reduced relative to that of the Control after 12 d. It is indicated that exogenous calcium can alleviate the damage to the PSII reaction center under drought stress to some extent.…”
Section: Discussionmentioning
confidence: 99%